2016
DOI: 10.3389/fncir.2016.00028
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Specific Sensory Cortical Areas by Segregated Basal Forebrain Cholinergic Neurons Demonstrated by Neuronal Tracing and Optogenetic Stimulation in Mice

Abstract: Neocortical cholinergic activity plays a fundamental role in sensory processing and cognitive functions. Previous results have suggested a refined anatomical and functional topographical organization of basal forebrain (BF) projections that may control cortical sensory processing in a specific manner. We have used retrograde anatomical procedures to demonstrate the existence of specific neuronal groups in the BF involved in the control of specific sensory cortices. Fluoro-Gold (FlGo) and Fast Blue (FB) fluores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 56 publications
(76 reference statements)
3
30
0
Order By: Relevance
“…Fig 5F shows the response of a neuron in the 40 ms following whisker stimulation (trials are sorted by the latency to the first evoked spike). We found that the average latency in the Off trials was shorter than the average latency in the On trials, in which the VChIs were optogenetically stimulated (Latency On 18.7 ± 1.1 ms, Latency Off : 16.9 ± 0.8 ms; paired t test, t [17] = 2.44, p = 0.03). This longer average latency provides additional evidence for the inhibitory effect of VChIs on the sensory response.…”
Section: Optogenetic Activation Of Vchis Inhibits the Sensory Responsmentioning
confidence: 73%
See 3 more Smart Citations
“…Fig 5F shows the response of a neuron in the 40 ms following whisker stimulation (trials are sorted by the latency to the first evoked spike). We found that the average latency in the Off trials was shorter than the average latency in the On trials, in which the VChIs were optogenetically stimulated (Latency On 18.7 ± 1.1 ms, Latency Off : 16.9 ± 0.8 ms; paired t test, t [17] = 2.44, p = 0.03). This longer average latency provides additional evidence for the inhibitory effect of VChIs on the sensory response.…”
Section: Optogenetic Activation Of Vchis Inhibits the Sensory Responsmentioning
confidence: 73%
“…The scatter plot in Fig 5D compares the average PSTH peak amplitude for the intermediate whisker deflections (0.6, 1.0, and 1.4 mm) between the light Off and On conditions. For this range of whisker deflections, there is a significant reduction in the peak PSTH response (Off: 17 ± 3 spikes/s, On: 14 ± 3 spikes/s; n = 18, paired t test, t [17] = 4.3, p = 0.0005). It has been reported that spontaneous whisking can cause ACh release in the cortex from BF cholinergic projections as well as activate local VIP + interneurons [16,38,39].…”
Section: Optogenetic Activation Of Vchis Inhibits the Sensory Responsmentioning
confidence: 91%
See 2 more Smart Citations
“…For example, VIP neurons inhibit PV neurons in the superficial layers of mouse auditory cortex (Letzkus et al, 2011; Pi et al, 2013), whereas such inhibition is not clearly observed in the visual cortex (Karnani et al, 2016; Pfeffer et al, 2013). Furthermore, cortical projections of BF are topographically organized (Zaborszky et al, 2015) and cholinergic modulation can be cortical area specific (Chaves-Coira et al, 2016; Golmayo et al, 2003; Rasmusson et al, 2007). Thus, cholinergic modulation can be task specific and also different tasks with varied cholinergic load could activate distinct cortical circuits (Chen et al, 2015).…”
Section: Discussionmentioning
confidence: 99%